2011
DOI: 10.1158/1940-6207.capr-11-0343
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded Protein Response Signaling and MAP Kinase Pathways Underlie Pathogenesis of Arsenic-Induced Cutaneous Inflammation

Abstract: Arsenic exposure through drinking water is a major global public health problem and is associated with an enhanced risk of various cancers including skin cancer. In human skin, arsenic induces precancerous melanosis and keratosis, which may progress to basal cell and squamous cell carcinoma. However, the mechanism by which these pathophysiological alterations occur remains elusive. In this study, we showed that sub-chronic arsenic exposure to SKH-1 mice induced unfolded protein response (UPR) signaling regulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 22 publications
2
51
0
Order By: Relevance
“…32 Earlier, we also found that the UPR pathway underlies the pathogenesis of subacute arseniteinduced mild inflammatory responses in the skin. 13 Therefore, together this provides a likely scenario that trivalent arsenic released from metabolic degradation of lewisite may play a significant role in the induction of ER stress. Interestingly, ER stresseregulated pathogenesis is not unique to the toxic manifestations of arsenicals but is important in the pathobiology of multiple diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Earlier, we also found that the UPR pathway underlies the pathogenesis of subacute arseniteinduced mild inflammatory responses in the skin. 13 Therefore, together this provides a likely scenario that trivalent arsenic released from metabolic degradation of lewisite may play a significant role in the induction of ER stress. Interestingly, ER stresseregulated pathogenesis is not unique to the toxic manifestations of arsenicals but is important in the pathobiology of multiple diseases.…”
Section: Discussionmentioning
confidence: 99%
“…13 Briefly, first-strand cDNA synthesis was performed using RT 2 First Strand kit (SABiosciences). PCR was performed with mouse inflammatory cytokines and receptor PCR Arrays on a 7500 fast real-time PCR system (Applied Biosystems, Foster City, CA) using RT 2 qPCR Master Mix.…”
Section: Pcr Arraymentioning
confidence: 99%
“…Western blots were performed as previously described (25). The integrated density of bands was measured with ImageJ software (http://rsb.…”
Section: Western Blotmentioning
confidence: 99%
“…ROS levels in lung tissues were measured using the chloromethyl derivative of 29,79-dichlorodihydrofluorescein diacetate (CM-H2DCFDA, c6827; Invitrogen Life Technologies, Grand Island, NY) as described previously (25).…”
Section: Measurements Of Rosmentioning
confidence: 99%
See 1 more Smart Citation